High Expression of TIMM17B Is a Potential Diagnostic and Prognostic Marker of Breast Cancer: TIMM17B as a Marker of Breast Cancer - Mingting Duan; Yun Ren; Jiwen Zhang; Tingting Zhang; Yanhong Wang; Hongyan Jia (Cellular and Molecular Biology, 2023)
Breast cancer (BC) is the most common malignant tumor in women. TIMM17B has been found to be related to the cell cycle. The purpose of this study was to explore the diagnostic and prognostic value of TIMM17B in BC and its correlation with tumor immune infiltration and ferroptosis. For this purpose, the transcription and expression profile of TIMM17B between BC and normal tissues was downloaded from The Cancer Genome Atlas (TCGA). To verify the expression of TIMM17B in BC, we analyzed it by immunohistochemical staining. The correlation between TIMM17B and clinical features was analyzed using the R package to establish a ROC diagnostic curve. The GSVA package was used to determine the relationship between TIMM17B gene expression levels and immune infiltration. The GDSC was used to predict the IC50 of the drug. Expression of TIMM17B in tamoxifen-resistant breast cancer cells was detected by protein immunoblot analysis. Results showed that the expression of TIMM17B in many kinds of malignant tumors was higher than that in paracancer, with a significantly high expression in BC (P < 0.001). We validated this result by analyzing tissue microarrays. ROC curve analysis showed an AUC value in TIMM17B of 0.920. The Kaplan–Meier method showed a better prognosis for patients with high expression of TIMM17B in basal BC than that of patients with low expression of TIMM17B (HR=2.32 (1.09-4.94), P=0.038). In addition, the expression of TIMM17B in BC was negatively correlated with the level of immune infiltration, Tcm cells, T helper cells, and immune targets such as CD274, HAVCR2, and PDCD1LG2. At the same time, the expression of TIMM17B in BC was significantly correlated with the drug resistance and the expression of GPX4 and other key enzymes of ferroptosis. Protein immunoblot analysis revealed high expression of TIMM17B in tamoxifen-resistant breast cancer cells. In conclusion, the expression of TIMM17B in BC was significantly increased, and it was related to immune infiltration, drug resistance and ferroptosis in BC. Our research shows that TIMM17B can be used as a diagnostic index of BC and one of the targets of immunotherapy.